Synthesis of end-functionalized alkyl α-(hydroxymethyl) acrylate ester ether dimer derived polymers via atom transfer radical polymerization - Ryskulova, Kanykei. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
In this research, end group modification, hydroxylation, of the cyclic polymers obtained by the atom transfer radical polymerization of the alkyl- α-(hydroxymethyl) acrylate ester dimers (RHMA) were targeted. The dimers were synthesized from the corresponding acrylates using the Extented Baylis-Hilman reaction. The RHMA derived cyclopolymers were then block copolymerized with acrylate comonomers and then allyl alcohol was added, both under atom transfer radical polymerization (ATRP) conditions, to obtain hydroxyl containing end-groups. This sequence of reactions was not successful in obtaining the desired hydroxyl containing cyclopolymers. The hydroxyl content of the polymers was analyzed by 31P-NMR. Since the above hydroxylation method failed with the cyclic polymers, to check the validity of the approach, the addition of allyl alcohol was carried out directly on the linear analogues of the dimers, t-butyl- and isobornyl acrylate. In the case of t-butyl acrylate end group modification seemed to be efficient, however the exact quantification of the end group needs further studies. The method seems to fail with the more bulky isobornyl acrylate.
Keywords: Polymeric composites.